Development of Cognitive and Non-Cognitive Diagnostic Assessment Instruments in Differentiation Learning For Class IV Primary School - Romlah, Romlah; Rosidin, Undang; Pramudiyanti, Pramudiyanti (Journal of Innovation and Research in Primary Education, 2025)
Educators' understanding of cognitive and non-cognitive diagnostic assessment instruments impacts the achievement of student competencies. To overcome this problem, cognitive and non-cognitive diagnostic assessment instruments are needed to identify learning needs, learning styles, and the potential and challenges of each student. This study aims to produce valid and practical cognitive and non-cognitive diagnostic assessment instruments in differentiated learning. This study is a type of Research and Development (R&D) research, its development is carried out referring to the theory of Borg & Gall. The sample in this study consisted of class IV A with 22 students and class IV B with 22 students at SDN 2 Sumur, Ketapang District, South Lampung Regency. The data collection techniques used were observation, interviews, questionnaires, and documentation. The data analysis technique used was the validity and practicality test of the cognitive and non-cognitive diagnostic assessment instruments. The results of the validation test of evaluation experts, material experts, and language experts on the cognitive and non-cognitive diagnostic assessment instruments obtained an average score of 82% with very valid criteria. The results of the practicality test of students' responses to the cognitive and non-cognitive diagnostic assessment instruments developed were stated to be practical with an average value of 89% and categorized as very practical. Conclusions: (1) The cognitive and non-cognitive diagnostic assessment instruments were proven to be valid in differentiation learning, and (2) The cognitive and non-cognitive diagnostic assessment instruments were proven to be practical in differentiation learning.